Exploratory Study on School Abandonment in Specialized Artistic Education (Supplementary Regime) - Gonçalves, Carlos (2019)
This article addresses the pupils’ dropout in vocational music education and was conducted at the Conservatory – School of Arts of Madeira (Portugal), using quantitative research methods. Different questionnaires were administered to participating groups (pupils, parents, teachers) and were statistically processed, in order to try to respond to the goals of the study: 1) analyse the related causes for enrolment into Specialized Artistic Education courses in music; 2) identify possible correlations between the variables; 3) understand how much the enrolment into Specialized Artistic Education is based upon vocational self-determination of the pupil; 4) relying on the analysis of main reasons for dropping out, identify primary intervention areas and the factors conducive to maintaining the enrolment in this artistic area. The discussion of these objectives results in some recommendations on improving the continuation rate of pupils in Specialized Artistic Education.